"Жизни каждое мгновенье": [стихотворения и лирическая проза] / Надежда Тронина - Тронина Надежда Николаевна (Удмуртия, 2015)
Экземпляры: ф.1 (20160208) / Инвентарный номер: 56838 / Цена: / Сис.шифр: 84(2Рос.Удм)6 / Авт.знак: Т 73 / ГРНТИ: 17.82.82 / ББК: 84(2Рос.Удм)6